REORIENTASI MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DAN DERADIKALISASI AGAMA - Syukur, Fatah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
Islamic religious education in schools substantively had a very important role. In accordance with the mandate of the Law on National Education System, religious education should be provided to learners at all levels of education. Religious education was expected not only to provide knowledge of religion, but also build the personality character of the students using religious values taught. Through quantitative research, this study examined the implementation of Islamic religious education in schools with the research problems: is there any correlation with religious observance, and any other factors that affect the behavior of religion? How does the orientation of Islamic religious educationin schools? The results showed that Islamic education is not positively correlated to the level of religious observance. Similarly, differences in men and women are not correlated to the level of religious observance. Therefore, there will be necessary reorientation of religious education in schools.***Pendidikan agama Islam di sekolah secara substantif memiliki peran yang sangat penting. Sesuai dengan amanat Undang-undang Sistem Pendidikan Nasional, bahwa Pendidikan Agama harus diberikan kepada peserta didik di semua jenjang pendidikan. Diharapkan Pendidikan Agama bukan hanya memberikan pengetahuan agama saja, akan tetapi juga membentuk karakter kepribadian anak didik dengan nilai-nilai yang diajarkan oleh agama. Melalui penelitian kuantitatif, tulisan ini mengkaji pelaksanaan Pendidikan Agama Islam di sekolah, apakah ada korelasinya dengan ketaatan beragama, adakah faktor-faktor lain yang berpengaruh terhadap perilaku beragama? Serta bagaimana orientasi Pendidikan Agama Islam di sekolah? Hasil penelitian ini menunjukkan bahwa Pendidikan Agama Islam tidak berkorelasi positif terhadap tingkat ketaatan beragama. Demikian pula perbedaan laki-laki dan perempuan tidak berkorelasi terhadap tingkat ketaatan beragama. Oleh karena itu, maka perlu ada reorientasi Pendidikan Agama di sekolah.